Guideline for Thailand Gems and Jewelry Industry Management to Modern Production Technology Management - Khotphathum, Phongphun (Journal of Buddhist Anthropology, 2021)
This research aims to (1) investigate important levels guideline for Thailand gems and jewelry Industry management to modern production technology management, and (2) to develop the structural equation model of the guideline for Thailand gems and jewelry Industry management to modern production technology management. This study employed both quantitative and qualitative research methods. The samples for qualitative research were 9 experts who came from top management in government sector, private sector and academic. The samples for quantitative research were 500 entrepreneurs in the gems and jewelry industry which got standard or award. The results revealed that the important level of the guideline for Thailand gems and jewelry industry management to modern production technology management was at high in overall. When considering in each dimension, including Product Design and Development, Machines and Equipment Automation Management, Quality Control and Continuous Improvement, and Production Planning and Control, the important level was at high in every dimension The analysis of the structural equation model had value over the minimum criteria and consistent with the empirical data. It can conclude that (1) machines and equipment automation management directly influence on product design and development, quality control and continuous improvement and production planning and control at statistically significant levels of 0.001, (2) product design and development directly influence on quality control and continuous improvement and production planning and control at statistically significant levels of 0.001, and (3) production planning and control directly influence on quality control and continuous improvement at statistically significant levels of 0.05.